Trend of the Research on Digital Nomads - Zrinka LACKOVIC VINCEK (Communications of International Proceedings, 2023)
Digital nomads have replaced they work in a conventional office and started to work and travel without a clear destination. They use their skills to work via internet, communicating through social networks, computers and mobile phones. Considering the rapidly growing trend of digital nomadism and the emerging literature on these theme, the purpose of this study is to analyze publications related to digital nomads based on the data obtained from the Web of Science core collection database. Using bibliometric approach, this paper analyzes the research productivity, paper type, research area, language of publications, distribution of publications by countries, authorship, keywords and citation analysis, based on the data gathered from VOSviewer software program. The results of the study show that in the period from 1996 until 2023 only in 2021 was recorded a significant increase concerning the literature on digital nomads. As of 3rd March 2023, there are 72 publications that have been conducted on digital nomads, published mostly in English, by a total of 102 authors from 24 different countries.
Keywords: digital nomads; digital nomadism; remote work; bibliometric analysis